FREEDOM OF EXPRESSION AND RIGHT TO PRIVACY IN THE EUROPEAN UNION: THE RIGHT TO PHOTOGRAPHS PRIVATE PROPERTIES - Sudharto, Alifia Qonita (UI Scholars Hub, 2014)
The debate to make a balance between exercising the freedom of expression and the right to privacy has never reached a global consensus, even among the European Union member states. In relation to the copyright law, there are no prohibitions or limitations in taking photographs, but the right to privacy has to be taken into account. The problems between the act of taking photographs and its limitation regarding the right to privacy have been increased to a new level with the development of copyright law, called the freedom of panorama, which might allow taking photographs of private properties without having to gain prior consent.